Burnout Syndrome and Sexual Disorders Among Vietnamese Female Nurses and Midwives at Tu Du Hospital: A Frontline Hospital-Based Cross-Sectional Study - Thanh Hai Pham; Minh Tuan Vo; Phuc Nhon Nguyen (Women's Health Reports, 2025)
Background: Burnout syndrome has become a great concern worldwide in recent decades. It can also lead to a negative effect on quality of work, life, and sexual dysfunction. This study assesses the prevalence of burnout syndrome and its association with sexual dysfunction among female nurses and midwives at a frontline hospital. Material and Methods: This cross-sectional study was conducted at Tu Du Hospital in Vietnam between February 1, 2023 and March 31, 2023. The study enrolled 485 female nurses and midwives. Among them, 426 women were eligible for the assessment of sexual disorders. This study used the Maslach Burnout Inventory–Human Services Survey toolkit to investigate burnout syndrome and the Female Sexual Function Index (FSFI) to determine sexual dysfunction. Results: Of the 485 respondents, the burnout rate was 27.0%, of which emotional exhaustion (EE), depersonalization, and diminished personal achievement (PA) were found at 13.2%, 6.0%, and 18.4%, respectively. Factors relating to burnout included young age, work duration of less than 10 years, sleep disorders, high workload, insufficient salary, and job dissatisfaction. Among 426 respondents completing the FSFI tool, 12.0% of female health care workers experienced sexual dysfunction, of which decreased sexual desire appeared in 42.0% of participants. EE at work was associated with sexual health issues and almost all sexual dysfunction factors with a weak negative correlation coefficient. Reduced PA was related to general sexual status, anorgasmia, and dyspareunia with a weak positive correlation coefficient. Conclusion: Overall, the prevalence of burnout and sexual disorders were 27.0% and 12.0%, respectively. Importantly, work-related factors were the main factors associated with burnout syndrome. EE and reduced PA were related to sexual disorders. These results underscore the need to assess support for the professional well-being of nurses and midwives. Further national-database studies are required to strengthen these findings.